Makerspaces on Social Media: Shaping Access to Open Design. (2nd September 2019) - Menendez-Blanco, Maria; Bjørn, Pernille
Abstract : Open Design is an emerging area of research that seeks to connect and extend the culture of making, social innovation, open-source software, and open-source hardware. A cornerstone for Open Design is to broaden participation in technology innovation by allowing people to use and contribute to publicly shared resources. Makerspaces are important access points to share and contribute to these resources. However, prior to entering the physical door of a makerspace, makerspaces' social media presence serve as the 'front door' for Open Design activities. In this paper, we examine different 'front doors' of Open Design, asking: What are the characteristics that produce makerspaces' social media presences, and how do these representations shape potential access to Open Design activities? We manually collected and qualitatively analyzed 500 public posts on the Facebook sites of five makerspaces in Copenhagen, Denmark. By choosing the same geographical area, we were able to explore the characteristics of makerspaces' social media presences for the same potential population of Open Design participants. Our analysis identifies three main characteristics of makerspaces' social media presence, which together shape access to Open Design activities, namely reach, transparency, and discourse. The display of these characteristics produce openness and availability in unique ways, and is constitutive for how Open Design activities are produced online. In this paper, we do not argue for or against specific social media representations. Instead, we argue that the specificities and differences between makerspaces' social media presences in the same geographical region have the strength of producing different identities across spaces, allowing for a broader definition and potential participation in Open Design.